(untitled) (Nepalese Veterinary Journal, 2017)
Study in blood parasitic diseases in dog was carried out from August 2014 to November 2014 to find out the prevalence of haemoparasites in clinical cases of hyperthermia in dogs. Blood sample from 50 cases of hyperthermia were collected and examined for any blood parasites by the smear method. The haematological parameter (RBC, WBC, PCV, Hb, & DLC) of each sample was also assessed and analyzed. Data was analyzed to determine prevalence of various species of blood parasites to establish the correlation of the infections with age, sex and breed. Out of 50 samples examined, blood parasites were determined in 12 percent samples of which 2(4%) were positive for Babesia canis and 4 (8%) were positive for Ehrlichia spp. The percentage of infection was greater in female 4(16.67%) than male 2(7.14%). The prevalence of blood parasite was higher in German shepherd. The prevalence of blood parasite was higher in 2-4 years of dogs. To determine significant difference between the hematological parameter of infected and non-infected cases, t-test was need (R, version 3.0.3). The confidence level for the analysis was set at 95percent with significance level assessed at p< 0.05. The study between the infected and non-infected host revealed statistically significant difference in PCV, Neutrophil and Eosinophil. Whereas other parameters did not have any significant difference. The mean PCV was significantly low (P <0.05) in infected dog than in non-infected dog. Mean Neutrophil was significantly decreased whereas Eosinophil was increased in infected dogs than in non-infected dogs.